The politics of employment liability. (1st September 2014) - Munyon, Timothy P.; Kane‐Frieder, Rachel E.
Summary Employment liability is an important check and balance against employee harm at work. In practice, however, an inadvertent consequence of employment liability is a potential shift in power from organizations to employees that affects subsequent managerial decision making. In this Incubator, we discuss behavioral and attitudinal ramifications of employment liability at work. Copyright © 2014 John Wiley & Sons, Ltd.